The Role of Transactional Leadership, Compensation and Working Environment on Employee Job Satisfaction in Fertilizer Industry - M. Yusuf Alfian Rendra Anggoro KR; Eka Kurnia Saputra; Lailatun Nafisa; Hermin Nainggolan; Ristawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of the study is to examine the effects of transactional leadership, the workplace, and employee compensation on employee happiness in the Indonesian fertilizer business. This study is quantitative in nature, collecting data through the use of questionnaires and supported by secondary sources of information (document). 83 employees made up the sample for this study utilizing the convenience sampling approach. Multiple linear regression is the technique analysis employed. According to the research, compensation, working conditions, and transactional leadership style all have a minimally significant impact on employee happiness. The working atmosphere, salary, and transactional leadership style all have a big impact on employee satisfaction. The working environment is the main influencing factor..